2020
DOI: 10.1016/j.ijinfomgt.2020.102119
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of digital service failure on users: Integrating Tan’s failure and DeLone and McLean’s success model

Abstract: Although information systems (IS) success has been given much attention in IS literature, failure has received lesser attention. This study empirically validates a model of digital service failure for consumers by integrating three dimensions from Tan's failure model and one dimension from DeLone and Mclean's Information Success model. The factors have been mapped to Expectation Disconfirmation Theory (EDT). Experiential survey approach has been used to collect primary data from information systems users who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 91 publications
1
26
1
7
Order By: Relevance
“…Information Risk Information risk plays an important factor in increasing the usage of digital services (Mustafa et al 2020). Digital payments services are required to maintain the integrity and authorization of transactions (Slade et al 2015).…”
Section: Theory Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Information Risk Information risk plays an important factor in increasing the usage of digital services (Mustafa et al 2020). Digital payments services are required to maintain the integrity and authorization of transactions (Slade et al 2015).…”
Section: Theory Developmentmentioning
confidence: 99%
“…Reduced information risk instils higher user confidence because users lower their apprehension of losing their personal information and financial information to external entities intentionally or accidentally (Leong et al 2003 ). Information risk factors could be triggered by economical, performance, social, time or financial triggers (Shon and Swatman 1998 ; Mustafa et al 2020 ). If the information risk increases, as perceived by the consumer, there is a greater chance that the consumer may not adopt or use the technology (Leong et al 2003 ; Slade et al 2015 ; Weerakkody et al 2017 ).…”
Section: Theory Developmentmentioning
confidence: 99%
“… Perceived severity is the level of the potential impact of the threat ( Vance et al, 2012 ) resulting from insufficient or ineffective ISS measures to manage the threat. This perception of potential impacts is important when considering suitable corrective actions to implement ( Mustafa et al, 2020 ) and reinforce the threat appraisal ( Siponen et al, 2014 ). …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, seen from a manager’s perspective, BYOD can harm the organization’s information system security and lead to failure. Failure can correspond to information failure (compromised data security), functional failure and system failure and can eventually lead to service failure from companies ( Mustafa, Kar, & Janssen, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While most of the literatures focused on the scalability of digitization, an important factor, security, has been overlooked, which has been discussed in Mir et al (2020). Another overlooked factor of digital inequality, the reasons behind the rejection of digital service, was investigated by Mustafa et al (2020). Their investigation results showed that the outcome and customers' satisfaction of digital services are greatly impacted by information, functional, system and service failure.…”
Section: Related Workmentioning
confidence: 99%